Ocean acidification in the Canary Current Large Marine Ecosystem - Santana-Casiano, J. Magdalena; González-Dávila, Melchor (IOC-UNESCO, 2015)
The Canary Current Large Marine Ecosystem (CCLME) covers a series of different oceanographic conditions which evolves from the open ocean to an upwelling coastal margin. In the Eastern Atlantic Ocean, the European Station for Time series in the Ocean (ESTOC) shows that the pH in total scale at in situ conditions presents a decrease of 0.0019 ± 0.0003 as a consequence of an increase in the seawater partial pressure of carbon dioxide (pCO2) of 1.9 ± 0.3 µatm yr-1. Most of the seasonal variability in pCO2 at the ESTOC is explained by the thermodynamic effect of changes in temperature. In the Mauritanian area, the pCO2 increased at a rate of 4.6 µatm yr-1 from 2005 to 2008, showing values higher than at the ESTOC. The seasonal pCO2 variability observed in the Mauritanian upwelling area has been highly correlated with the upwelling index and it is higher than that observed at the ESTOC. Due to the heterogeneity of the CCLME it is not possible to generalize the observed trends. The rate of decrease of pH in the upwelling areas is the result of complex processes. These are determined by the intensity of the upwelling that can be modified by the variations in oceanographic conditions as a result of climate change. Published